Trends in solids/liquids poisoning suicide rates in Taiwan: a test of the substitution hypothesis - Lin Jin-Jia; Lu Tsung-Hsueh (BMC, 2011)
Abstract Background Several previous studies have illustrated that restricting access to lethal methods can reduce suicide rates. The most often cited example was Kreitman's study, showing a reduction not only in gas-specific suicide rates, but also in the overall suicide rates because of the lack of increase of other methods. However, method substitution is still a major concern in the application of the means restriction strategy to prevent suicide. The aim of the study was to investigate whether the reduction in the solids/liquids poisoning suicide rate in 1983-1993 after the launching of pesticide restriction interventions in Taiwan was accompanied with an increase in the suicide rate using other methods (method substitution). Methods Data on age-, sex- and method-specific suicide rates for 1971-1993 in Taiwan were obtained. Changes in solids/liquids poisoning suicide rates were compared with suicide rates by hanging and other methods between 1983 and 1993. Results No concomitant increase in suicide rates by hanging or other methods was noted from 1983 to 1993, during which the suicide rates by poisoning with solids/liquids (mainly pesticides) decreased markedly and steadily. The phenomenon of method substitution was also not found by sex and age groups. Conclusion In general, no method substitution was found along with the reduction in solids/liquids suicide rates in Taiwan. Our study results have also added the evidence that restricting access to methods maybe a promising strategy in preventing suicide, particularly in those countries where the "target method" has been found to contribute greatly to the suicide rates.